Economic Democracy and the Quest of Net Neutrality in Indonesia - Azis, Arasy Pradana A. (Lentera Hukum, 2021)
Net neutrality has played critical issues in internet-based businesses, as it may stop Internet Service Providers (ISPs) from discriminating against certain legal internet contents, platforms, or services. This study argued that net neutrality has a strong relationship with economic democracy as the constitutional basis of the Indonesian economy. This study examined net neutrality and considered its possible adoption in Indonesia under economic democracy by justifying economic democracy required the state to build an inclusive economy as per political economy theory. It used a socio-legal method through an interdisciplinary study of law and political economy with conceptual and comparative approaches. The study showed that the idea of the internet as a level playing field was founding net neutrality. For instance, in the United States and across different Global South countries, net neutrality relied on three orders of no blocking, no throttling, and no paid prioritization, which provided equal access for everyone to create their opportunities. At this point, economic democracy and net neutrality made their cross-cut. Like net neutrality, a discriminatory action against a content provider violated economic democracy, where policy-makers formulated economic policies to enable a level playing field for economic actors. Minimum barriers to entering the market might create such a level playing field. Without net neutrality, ISPs could carry out arbitrary actions and abuse of power for business interests. This study concluded that the adoption of net neutrality into formal regulation created a positive climate of innovation in the digital business ecosystem in Indonesia. KEYWORDS: Economic Democracy, Net Neutrality, Digital Economy.